The State and Prospect of Legislation Number 39 Year 1999 of Indonesia - Mendy, Ousu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
As national politics continues to have influence on human rights both in practice and theory globally, Indonesia also finds itself in a conundrum of human rights challenges. Like other legal entities that have ratified international instruments that deal with human rights, Indonesia has ratified, acceded to and domesticated relevant human rights instruments. At national level, Indonesia also has Legislation Number 39 of Year 1999 (hereinafter referred to as Law No. 39 of 1999) which deals with human rights. This research examines the failure or inability of this law to control the political elites over the years. It examines the influence of the Indonesian society on this legislation. Its ius constitutum is analyzed and thereafter, points out the ius constituendum as a prospect for a progressive society. In this research, a normative research method is used through analysis of authentic secondary data. This, therefore, reaches a finding that Indonesia’s international human rights diplomacy should be strengthened at the level of Ministry of Foreign Affairs with technical support from the Ministry of Law and Human Rights. Going forward, strong advocacy policy on human righs across all the regions in Indonesia also needs to be in place by the government.